Cardiac resynchronization therapy adjustment during the cardiopulmonary testing: Study protocol - Stutz, Kelly Christine; de Tarso Jorge Medeiros, Paulo; Bellotti Lopes, Hugo; Vinicius de Oliveira Montesi, Marcos; Alberto Cordeiro Hossri, Carlos; Mirelli de Melo Viana, Renata; Amorim Souza Leão, Marilia (Manual Therapy, Posturology & Rehabilitation Journal, 2022)
Background: Cardiac resynchronization therapy is known to promote symptom improvement, increased survival, and decreased hospitalizations for heart failure. However, one third of patients on cardiac resynchronization therapy may not achieve any clinical improvement. One of the factors for the lack of improvement is an inadequate adjustment of the cardiac device programming, because such adjustments are commonly made at rest. Cardiac resynchronization therapy optimization can be done by adjusting the cardiac resynchronizer during cardiopulmonary exercise testing, this allow the program to align with the functional class of the patient, thus maintaining atrioventricular synchronism and biventricular pacing according to the chronotropic response to effort. However, there is a lack of protocols that propose device adjustment through cardiopulmonary exercise testing and that evaluate the response to its readjustment. Objective: To develop a cardiac resynchronizer readjustment protocol using cardiopulmonary exercise testing. Methods: This was a randomized controlled clinical trial to evaluate the effectiveness of device readjustment during maximal exercise. The variables used to measure the degree of response to readjustment will be: Functional capacity by the six-minute walk test, life quality by means of the Minessota questionnaire and sleep quality by means of the pittsburg. Participants will be divided into two groups (control and intervention group), then, the six-minute walk test will be applied, followed by life quality and sleep evaluation. The cardiopulmonary test will be the last proposed activity and will not be performed on the same day as the other evaluations. After three months, they will be submitted again to the same testes mentioned previously. During the initial evaluation by cardiopulmonary testing, the components of the intervention group will undergo cardiac resynchronization readjustment by means of a protocol. Results: We hope that the intervention designed by the protocol can contribute to the improvement of functional capacity, quality of life and sleep.